Dostosowanie systemów oceny ryzyka kredytowego do wymagań nowej bazylejskiej umowy kapitałowej - Bryndza, Joanna (Credit Risk Analysis Systems Adaptation to New Basel Capital Accord, 2005)
The New Basel Capital Accord introduces requirements in the face of banks. The requirements concern risk management and credit activity. In the article are fundamental resolutions presented and changes that banks should introduce, especially in analysis systems and credit scoring.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 90-97